Exploring the potential of complementary determining region (CDR) transplant towards fibronectin scaffold through molecular dynamics simulations - Soen, Min Wen (2018)
This thesis deals with the molecular dynamics method to study the dynamics of the Fibronectin scaffold and with and without transplanting Complementary Determining Region Loops.